Pretrial of the Seizure of Property Unrelated to Criminal Offenses: Between the Interests of Corruption Eradication and the Protection of Human Rights - Wicaksana, Prasetyo Budi; Hassan, Fareed Mohd (Universitas Muhammadiyah Purwokerto, 2026)
Asset seizure in corruption cases is an important instrument in efforts to recover state financial losses. However, in law enforcement practice, seizures are often carried out against goods or property that have no causal relationship with the alleged criminal offense. This condition creates tension between the interest of eradicating corruption and the protection of human rights, particularly the right to property and the guarantee of due process of law. This article aims to analyze pretrial remedies against the seizure of property unrelated to corruption offenses from the perspectives of law enforcement and human rights protection in Indonesia. This study employs a normative legal research method using statutory, conceptual, and case approaches, particularly through an examination of pretrial decisions of the Pekanbaru District Court concerning asset seizures in alleged corruption cases. The results indicate that seizures not supported by evidence of a direct connection to the criminal offense potentially violate the principle of legality, the principle of proportionality, and the protection of human rights as guaranteed by the 1945 Constitution of the Republic of Indonesia and national human rights instruments. Pretrial mechanisms play a strategic role as a form of judicial control over arbitrary coercive measures. Therefore, reforms are required in the seizure application mechanism by emphasizing strict substantive review and strengthening the role of pretrial proceedings to create a balance between the effectiveness of corruption eradication and the protection of citizens’ constitutional rights within the Indonesian criminal justice system.